Enhancing Agricultural Export Performance: The Role of South Sulawesi's Paradiplomacy in Expanding Trade with Egypt - Anugrah, Muhammad Yoga Dwi; Halifa Haqqi; Pinandoyo, Dimas Bayu (Journal of Paradiplomacy and City Networks, 2024)
This study provides an in-depth analysis of how the South Sulawesi Provincial Government's paradiplomacy initiatives have impacted agricultural product exports to Egypt. The research employs a conceptual framework integrating Paradiplomacy and International Trade, aiming to assess the effects of these policies on export volumes. Utilizing a descriptive research methodology, the study elucidated the strategies and roles adopted by the regional government in promoting exports. Key findings indicated that South Sulawesi engages in global paradiplomacy, functioning as a facilitator to enhance export performance. Effective promotional strategies identified included personal selling, public relations through webinars and training sessions, and participation in trade exhibitions. By applying the concept of global diplomacy, the Government of South Sulawesi Province can use its autonomy to establish trade relations and expand market access to Egypt, thereby improving the export performance of local agricultural products. The research highlights the crucial role of regional governments in boosting agricultural exports through infrastructure development and service improvements. By adopting global paradiplomacy, the South Sulawesi Government has successfully established trade relations and expanded market access to Egypt, resulting in a notable increase in agricultural export volumes. This study underscores the significant positive contributions of paradiplomacy to regional economic growth through international trade expansion.